P218 The effects of supplemental oxygen on blood pressure in obstructive sleep apnoea during cpap withdrawal. (15th November 2017) - Turnbull, CD; Petousi, N; Sen, D; Stradling, JR; Kohler, M
Abstract : Introduction: Intermittent hypoxia and/or intermittent arousals are thought to be the two key pathological mechanisms in the development of hypertension in obstructive sleep apnoea (OSA). We aimed to investigate the effect of abolishing the hypoxia on the rise in blood pressure (BP) that has been shown to follow continuous positive airway pressure (CPAP) withdrawal in patients with OSA. In addition, we explored the effect of supplemental oxygen on obstructive events during sleep. Methods: Patients with OSA, established on CPAP≥1 year, and with ≥4 hours/ night usage, underwent a week of screening oximetry and were eligible if they had a nocturnal oxygen desaturation index ≥4% (ODI) of <10 on 3 nights on CPAP, and an ODI≥20 on at least 1 of 4 nights off CPAP. Patients then received overnight supplemental oxygen or air (via real or sham concentrators) at a flow rate of 5 l/min during 2 weeks off CPAP. After at least two weeks 'washout' back on CPAP, subjects crossed over. Treatment order was randomised. The primary outcome was early morning home BP which was recorded daily in triplicate, and averaged over the penultimate three mornings prior to each patient visit. Patients underwent overnight home respiratory sleep studies (including nasal airflow) on night 14 of each treatment arm. Differences between treatment arms were analysed using paired t-tests or Wilcoxon rank tests as appropriate. Results: Twenty-five patients completed the study. Their mean ±standard deviation age was 63±7 years, mean BMI was 35.3±6.7 kg/m 2, median (interquartile range) ODI at diagnosis was 48/hour (25, 68), and 21 (84%) were male. Table 1 shows the Results of the primary outcome and the overnight sleep studies. Discussion: Supplemental oxygen abolished the rise in early morning blood pressure during CPAP withdrawal when compared to supplemental air. As expected, supplemental oxygen substantially attenuated intermittent hypoxia and had only a small non-significant effect on the apnoea hypopnoea index. Thus intermittent hypoxia appears to be the dominant determinant of the rise in morning blood pressure seen in patients with OSA, rather than any other consequence of the obstructive events.